'Stay Safe, Stay Home': Spatial Justice in the Pandemic City. Issue 1 (March 2021) - Young, Alison
Abstract : How does spatial justice take place within cities? To understand spatial justice within a city under lockdown, this article considers both the 'corporeal emplacements' within spaces identified by Philippopoulos-Mihalopoulos (2015) and the 'material geographies' ( Soja 2010 ) essential to understanding spatial justice in everyday life in contemporary cities. Several of the material localities arising during the 'stay home' orders of the State of Emergency in Victoria are considered; namely, first, the shared spaces of the street visited by individuals on their permitted forays from home; second, the domestic space of the home; third, the spaces occupied by or allocated to those who lack stable housing; and, finally, hotel rooms, used during the pandemic to house people experiencing homelessness, returned travellers in quarantine, and evacuated detainees. Close examination of such places reveals fault lines of social stratification, linguistic and representational boundary lines regulating their governance, and the stakes of seeking to achieve spatial justice in the pandemic city.